2002
DOI: 10.1046/j.1365-2672.2002.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro bifidogenic properties of pectins and pectic-oligosaccharides

Abstract: Aims: To compare the in vitro fermentation properties of pectins and oligosaccharides derived from them in pure and mixed faecal cultures. Methods and Results: Specific growth rates of selected bacterial genera were calculated in pure culture. Bifidobacterium angulatum, B. infantis and B. adolescentis had higher growth rates on pectic oligosaccharides (POS I) derived from high methylated pectin (HMP) than on HMP and B. pseudolongum and B. adolescentis on pectic oligosaccharides (POS II) derived from low methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
4
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 34 publications
(68 reference statements)
6
151
4
5
Order By: Relevance
“…It is thought that this is due to the reduction of pathogenic bacteria such as Shigella, Salmonella, Klebsiella, Enterobacter, Proteus and Citrobacter from intestine. This is supported by Olano-Martin et al (2002) who observed that pectin stimulated the growth of certain strains of Bifidobacteria and Lactobacillus in vitro. These bacteria are considered to be directly related to the health of the large intestine and their concentrations depict a healthy microflora population.…”
Section: Pectin and Detoxificationmentioning
confidence: 54%
“…It is thought that this is due to the reduction of pathogenic bacteria such as Shigella, Salmonella, Klebsiella, Enterobacter, Proteus and Citrobacter from intestine. This is supported by Olano-Martin et al (2002) who observed that pectin stimulated the growth of certain strains of Bifidobacteria and Lactobacillus in vitro. These bacteria are considered to be directly related to the health of the large intestine and their concentrations depict a healthy microflora population.…”
Section: Pectin and Detoxificationmentioning
confidence: 54%
“…This is due to the high degree of methoxylation of the pectin used in this study (Sigma-Aldrich, 2006). Methoxylation decreases the growth rate of pectin-fermenting bacteria (Olano-Martin et al, 2002). The methyl group can be esterified with a release of methanol (Drochner et al, 2004) but, unlike glucuronic acid, the methyl group is unusable by pectinolytic bacteria (Hall and Herejk, 2001) for ATP generation and growth.…”
Section: Figurementioning
confidence: 99%
“…Also, the cost of producing prebiotic materials such as XOS becomes 45% lower than that of other conventional fruit pulp industries as shown in the earlier research (Olano-Martin et al, 2002). Hence, the current research prefers XOS production from orange fruit wastes.…”
Section: Introductionmentioning
confidence: 81%